Rapid responses of adipocytes to iron overload increase serum TG level by decreasing adiponectin. Issue 11 (14th April 2021) - Tang, Yuxiao; Wang, Dongyao; Zhang, Hongwei; Zhang, Yinyin; Wang, Jie; Qi, Ruirui; Yang, Jianxin; Shen, Hui; Xu, Yan; Li, Min
Abstract: Iron overload is tightly connected with metabolic disorders. Excess iron in the adipose and its roles in dyslipidemia are of interest to be identified. In acute iron overload mice receiving intraperitoneal injection of 100 mg/kg/day dextran‐iron for 5 days, the epididymis adipose showed a remarkable increase in iron. Serum triglyceride and low‐density lipoprotein cholesterol (LDL‐C) levels were increased and high‐density lipoprotein cholesterol (HDL‐C) level was decreased, while serum alkaline phosphatase, aspartate aminotransferase, glucose, and insulin were not affected. The serum‐cytokine‐microarray showed that adipocytokines, including adiponectin, leptin, and resistin were significantly decreased. Other serum cytokines, including pro‐insulin cytokines, inflammatory cytokines, chemokines, and growth factors were not changed, except that ghrelin and chemokine RANTES were increased. Iron overload decreased expressions of adiponectin and leptin both in vivo and in vitro. Intraperitoneal injection of recombinant leptin at 1 μg/g in acute iron overload mice had no significant effects on serum levels of TC, TG, HDL‐C, and LDL‐C, while intraperitoneal injection of recombinant adiponectin at 3 μg/g partially restored serum TG level through improving activities of lipoprotein lipase and hepatic lipase, but abnormal serum LDL‐C and HDL‐C were not redressed, suggesting other mechanisms also existed. In conclusion, the adipose responds to iron overload at an early stage to interfere with lipid metabolism by secreting adipocytokines, which may further affect glucose metabolism, inflammation, and other iron overload‐induced effects on the body. Abstract : Iron overload in adipocytes inhibits adiponectin synthesis, leading to decreases of serum adiponectin level, lipoprotein lipase (LPL), and hepatic lipase (HL) activities, thus induces elevation of serum triglyceride level.